2014
DOI: 10.5630/jans.34.103
|View full text |Cite
|
Sign up to set email alerts
|

The Effects on Clinical Nurses When Working with Nursing Practicum Students in Psychiatric and Mental Health Hospital

Abstract: Objective: e aim of this study was to nd out what e ects nurses experienced when working with nursing practicum students in clinical training. e study was conducted at a psychiatric hospital. Subjects and Methods: Face-to-face interviews with 4 nurses who participated in practice unit and a group interview with other medical sta in the ward were conducted and data was analyzed qualitatively. In addition, self-report questionnaires asking about job stress and burnout responses were given to 30 nurses in the war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The results revealed that the RAQ-7 scores of psychiatric nursing directors were higher than those reported for psychiatric nurses in previous studies (Chiba et al, 2016;Fujino & Fujimoto, 2016). The scores were lower than those for clinical psychologists and occupational therapists, comparable to those for social workers, and higher than those for doctors (Chiba et al, 2016) Although the proportion of assistant nurses in Japanese psychiatric hospitals is high (Nagai & Hashimoto, 2014), all the directors of the nursing department are nurses, and it is thought that the scores differed depending on the education they received.…”
Section: Discussionmentioning
confidence: 91%
“…The results revealed that the RAQ-7 scores of psychiatric nursing directors were higher than those reported for psychiatric nurses in previous studies (Chiba et al, 2016;Fujino & Fujimoto, 2016). The scores were lower than those for clinical psychologists and occupational therapists, comparable to those for social workers, and higher than those for doctors (Chiba et al, 2016) Although the proportion of assistant nurses in Japanese psychiatric hospitals is high (Nagai & Hashimoto, 2014), all the directors of the nursing department are nurses, and it is thought that the scores differed depending on the education they received.…”
Section: Discussionmentioning
confidence: 91%